Pós-tratamento de efluente do cozimento para laminação de toras de Pinus spp. por coagulação e filtração adsortiva - Claus, Luana Falbot (2019)
Plywood industry occupies a large space in the national economy, however, one of the problems faced by manufacturing process is the large volume of waste generated, such as liquid effluents generated during the wood cooking process. This cooking effluent presents high organic load, high apparent color and a huge quantity of phenolic compounds, which is typically toxic and bio-recalcitrant to conventional treatment systems as the stabilization ponds. Therefore, the present study aims to evaluate the removal of color, turbidity and phenol of the wood cooking effluent using chemical coagulation followed by adsorptive filtration on granular activated charcoal and natural zeolite. The tests were carried out on bench scale using a Jar-test apparatus. Effluent samples were collected at the company's wastewater treatment plant. The effluent A was the final effluent of the aeration pond, and the effluent B was the final effluent of the sedimentation pond. The study was carried out in two phases: in the first one, it was performed the investigation of the optimal operational conditions for coagulation process. It was investigated the coagulant dosage and sedimentation time. In the second phase, it was evaluated the efficiency of the coagulation treatment under the optimal conditions (optimized in phase 1). Then, the coagulated effluent was filtered on granular activated charcoal and natural zeolite. The results obtained in phase one indicated that the optimal condition for effluent A was coagulant dosage of 125 mg.L-1 along with sedimentation time of 40 min, and for the effluent B it was 125 mg.L-1 along with sedimentation time of 20 min. In phase 2, after chemical coagulation, effluent A showed a removal of 100%, 97%, 99%, 79% and 84% for BOD, color, turbidity, COD and phenol, respectively, effluent B showed removal of 100%, 99%, 98%, 80% and 85% for the same parameters, respectively. After the filtration of effluent A on activated charcoal, it was obtained removal of 90% of absorbance in 254 nanometers and 89% of suspended solids, besides significant removals for the other parameters. Effluent A filtered on zeolite reached removal of 74%, 76% e 89% of color, turbidity and suspended solids, respectively. Coagulation process showed to be an efficient process to the wood cooking effluent treatment. Filtration with both, activated charcoal and zeolites, allowed to improve the final effluent quality and showed optimistic results for later studies seeking the reuse of the treated effluent.